Surgical treatment of trigeminal neuralgia: a cohort study - Calderón García, Miguel André; Duarte Mora, Diana Paola; Jiménez Ponce, Fiacro (Revista Argentina de Neurocirugía, 2025)
Background: trigeminal neuralgia (TN) is a severe unilateral facial pain syndrome that follows the distribution of one or more branches of the fifth cranial nerve. Its impact on quality of life is substantial, restricting daily activities and contributing to the development of psychiatric disorders in affected patients. Objectives: to report our institution’s experience in the surgical management of TN, assessing its efficacy and safety. Methods: a retrospective analysis of the cases that underwent surgery in a one-year period following the COVID-19 pandemic was performed. Clinical follow-up was performed at 1, 3, 6, and 12 months postoperatively. Results: a total of 17 patients were included. The mean preoperative pain score was 9.06 (SD 1.43), which decreased to 2.12 (SD 3.04) in the immediate postoperative period (p < 0.0001). Pain recurrence was observed in 5 patients (29.4%), whereas in the remaining 12 patients (70.5%), pharmacological treatment was either reduced or completely discontinued. Conclusion: surgical intervention is indicated for TN refractory to medical treatment. The outcomes observed in our institution align with those reported in the international literature, demonstrating a high success rate in pain reduction and optimization of pharmacological management.